(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to investigate the prevalence of new-onset atrial fibrillation (AF) utilizing 7-day Holter electrocardiography (ECG) in elderly patients with coronary artery disease (CAD). Method: A descriptive, cross-sectional, prospective study was conducted involving patients aged ≥60 years diagnosed with CAD who were admitted to the Department of Interventional Cardiology at Thong Nhat Hospital from January 2023 to May 2023. A 7-day Holter ECG monitoring device was attached to each patient prior to discharge. Results: The study comprised 40 patients, with an average age of 72.6 ± 7.6 years. The male-to-female ratio was 52.5% to 47.5%. All subjects presented with a predominant sinus rhythm, exhibiting a mean heart rate of 72.4 ± 8.1 beats per minute prior to inclusion in the study. New-onset atrial fibrillation was detected in four cases (10%). Specifically, one case manifested on the third day of monitoring, two cases on the fourth day, and one case on the fifth day. Conclusion: The incidence of new-onset atrial fibrillation is notably prevalent among elderly patients with coronary artery disease. All detected instances were classified as paroxysmal atrial fibrillation, emerging from the third day onwards. This finding underscores the potential efficacy of 7-day Holter ECG monitoring compared to the conventional 24-hour Holter ECG in identifying atrial fibrillation in high-risk patient populations.